1994
DOI: 10.1183/09031936.94.07071290
|View full text |Cite
|
Sign up to set email alerts
|

Central bronchiectasis in allergic bronchopulmonary aspergillosis: comparative evaluation of computed tomography of the thorax with bronchography

Abstract: Demonstration of central bronchiectasis (CB) with normal peripheral bronchi is an essential requirement for the diagnosis of allergic bronchopulmonary aspergillosis (ABPA). Although the results of bronchography remain the gold standard for demonstration of central bronchiectasis they are not always diagnostic. Moreover, it is an unpleasant invasive procedure which may be difficult to perform in a patient of allergic bronchopulmonary aspergillosis with acute severe asthma. In an attempt to find a safe and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Hansell et al [33] were the first to describe CB arbitrarily as dilated bronchi within a point midway radially from the hilum to the chest wall. Subsequently, authors have used different definitions including subjective criteria based on proximity to the hilum [13] , and dilated bronchi within the medial two-thirds of the point radially from the hilum to the chest wall [14,16,17] . Although believed to be a characteristic finding in ABPA, the significance of CB as a specific diagnostic marker for ABPA is debatable as it has been shown that almost 40% of the involved lobes have bronchiectasis extending to the periphery [19,21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hansell et al [33] were the first to describe CB arbitrarily as dilated bronchi within a point midway radially from the hilum to the chest wall. Subsequently, authors have used different definitions including subjective criteria based on proximity to the hilum [13] , and dilated bronchi within the medial two-thirds of the point radially from the hilum to the chest wall [14,16,17] . Although believed to be a characteristic finding in ABPA, the significance of CB as a specific diagnostic marker for ABPA is debatable as it has been shown that almost 40% of the involved lobes have bronchiectasis extending to the periphery [19,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…To compare the HRCT chest findings of our study with those described in the literature, we have also performed a systematic review of PubMed and EmBase using free text search terms: allergic bronchopulmonary aspergillosis, ABPA. Our search yielded 3133 references of which 10 studies have reported HRCT chest findings of ABPA (Table 4) [ [13][14][15][16][17][18][19][20][21][22] . The studies have used different protocols for performance of CT, and most studies have used the definition of CB as dilated bronchi present within the medial two-thirds of the lung fields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed tomography has a sensitivity of 83% and a specificity of 92% in detecting central bronchiectasis in patients with ABPA [23]. Computed tomography appearances can be sub-divided into bronchial, parenchymal and pleural abnormalities.…”
Section: Discussionmentioning
confidence: 99%